A critical review on recent progress, open challenges, and applications of corrosion-resistant superhydrophobic coating. (March 2023) - Gupta, Rajeev; Verma, Rajeev; Kango, Saurabh; Constantin, Antoine; Kharia, Pulkit; Saini, Ritesh; Kudapa, Vamsi Krishna; Mittal, Ajay; Prakash, Jai; Chamoli, Pankaj
Abstract: Corrosion, an undesirable phenomenon, negatively affects the desirable properties of materials and has become a serious problem in various industries. Prevention of corrosion is a great challenge but very important for economical and technological growth. In this regard, superhydrophobic surfaces (SHSs) have gained enormous research interest due to their broad industrial applications. However, more in-depth knowledge is required to explore SHSs for real practical applications. There is a need for introducing simple and cost-effective fabrication techniques and tailoring of surface properties such as roughness, and surface morphologies important for improving the durability robustness characteristics. The present review focuses on recent developments in the fabrication of SHSs with different approaches, its applications, challenges, and future perspectives, especially in the anti-corrosive application. Graphical Abstract: ga1